Clinical Outcomes of Total Hip Arthroplasty With the Anterolateral Modified Watson-Jones Approach for Displaced Femoral Neck Fractures. (11th October 2022) - Takemoto, Naoki; Nakamura, Takuya; Kagawa, Katsura; Maruhashi, Yoshinobu; Sasagawa, Takeshi; Funaki, Kiyonobu; Aikawa, Takao; Yamamoto, Daiki
Objective: In recent years, many studies have reported good results with total hip arthroplasty (THA) for displaced femoral neck fractures (FNFs). However, no study has reported the clinical outcomes of the anterolateral modified Watson–Jones THA (MWJ-THA) for displaced FNFs. This study aimed to investigate the clinical results of THA for displaced FNFs at our hospital and to discuss the advantages of MWJ-THA over THA with other approaches for displaced FNFs. Methods: Forty-three patients who underwent MWJ-THA for displaced FNFs were included in this study. Patient characteristics, preinjury walking ability, activities of daily living, implants used, walking ability (at 1, 3, and 6 months after surgery), cup placement angle, clinical hip score, surgical complications, revision surgery, and death within 1 year after surgery were investigated. Results: The mean age of the 43 patients was 63.3 years, and the mean body mass index (kg/m 2 ) was 21.1. Regarding the heads used, 28-mm heads were used in 4 patients, 32-mm heads were used in 32 patients, and 36-mm heads were used in 7 patients. The cups were placed in the Lewinnek safety zone (93.0%). Four patients had stem sinkage of a few millimeters. 6 months postoperatively, 38 patients walked unaided, and 4 patients walked with a cane. The Harris Hip Score averaged over 90 points at all time points. No postoperative dislocation was observed. Two patients died within 1 year postoperatively. Conclusion: In this study, MWJ-THA was performed for displaced FNFs and resulted in no postoperative dislocations. Furthermore, more than 90% of the patients regained their preinjury walking ability at 6 months postoperatively. MWJ-THA has great dislocation control and is effective in treating displaced FNFs.